1989
DOI: 10.1128/mcb.9.5.1969
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine induction of major histocompatibility complex class I antigen expression results from induction of beta interferon in oncogene-transformed BALB/c-3T3 cells.

Abstract: By varying growth conditions, we identified a novel mechanism of autocrine regulation of major histocompatibility complex (MHC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…6C). In agreement with our previous findings (34,35), we found that C. trachomatis induces the release of IFN-␤ from human primary fibroblasts (3.5 Ϯ 3.1 IU/ml at 48 h after infection, n ϭ 3), which is known to play a critical role in the induction of MHC I expression (36). The addition of neutralizing antibodies directed against (Fig.…”
Section: Resultssupporting
confidence: 80%
“…6C). In agreement with our previous findings (34,35), we found that C. trachomatis induces the release of IFN-␤ from human primary fibroblasts (3.5 Ϯ 3.1 IU/ml at 48 h after infection, n ϭ 3), which is known to play a critical role in the induction of MHC I expression (36). The addition of neutralizing antibodies directed against (Fig.…”
Section: Resultssupporting
confidence: 80%
“…It deserves mention that a Ras-PKR connection (not in the context of viral infection) has been noted previously by Mundschau andFaller (1992, 1994). Based on the previous observation that introduction of a transforming Ras gene into BALB/c-3T3 fibroblasts blocks induction of responsive genes by platelet-derived growth factor and interferon (Zullo and Faller, 1988;Offermann and Faller, 1989), these investigators examined the effect of transforming Ras genes on PKR activity in these cells. Their results indicate that dsRNA-mediated activation of PKR is blocked in these transformed cells and that the block is at the level of activation of autophosphorylation, and not PKR synthesis (Mundschau and Faller, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…molecules. Associative recognition of target cells by CTL depends on the expression of both class I MHC glycoproteins and foreign antigenic determinants on the target cells, therefore it seems reasonable to believe that modulation of either one is a potential mechanism of tumor escape from immune destruction [12,19,20,31,38,40]. Indeed, in acute measles virus infection of neuroblastoma cells, where the expression of H-2K molecules was down-regulated [21], down-regulation of H-2K was inversely correlated with measles virus antigen expression on the cell surface and was associated with decreased susceptibility to lysis by allospecific CTL.…”
Section: Discussionmentioning
confidence: 99%